ANALISIS DAMPAK PROGRAM PENGEMBANGAN TANAMAN PERKEBUNAN KA-KAO TERHADAP KONDISI SOSIAL EKONOMI PETANI KAKAO DI KABUPATEN BOLAANG MONGONDOW UTARA (Analysis of the Impact of Cacao Plantation Plants Development Program of Social Economic Condition of Cacao Farmers in North Bolaang Mongondow District) - Juwita Janeke Eman; Rine Kaunang; Sherly G. Jocom (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This research was conducted in North Bolaang Mongondow Regency. Primary data were obtained from direct observation and interviews with respondents, namely cocoa farmers, farming communities and village government officials which were selected using purposive sampling method. While secondary data were obtainedÂ from related agencies. The purpose of this study was to observe and measure the impact of the cocoa plantation development program on the socio-economic conditions of farmers. Credibility test was used to test the validity of research data; triangulation method was used to see the social conditions of cocoa farmers; and tabulation, percentage and T test were applied to see economic conditions.From the results of the analysis, it could be seen that the cocoa plantation development program had a significant impact on the surrounding community, especially the beneficiary farmers because it had changed social conditions including health, beliefs, norms, networks, and patterns of cocoa cultivation. In addition, it provided changes to economic conditions including an increase in the type of housing and an increase in farmers' income.